Implementing Differentiated Learning Model in Enhancing Quran and Hadith Understanding at Madrasah Tsanawiyah Babussalam Rungkang - Ika Suryani; Sri Murniati (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This research aims to explore the implementation of a differentiated learning model in enhancing the understanding of the Quran and Hadith at Madrasah Tsanawiyah Babussalam Rungkang. Differentiated instruction is a pedagogical approach that tailors teaching methods and materials to accommodate diverse learning styles, abilities, and interests of students. The study focuses on how this model can address the varying levels of comprehension and learning needs in Islamic studies, particularly in the subjects of Quran and Hadith. The research employs a qualitative approach using classroom observations, interviews, and student performance assessments to collect data. The findings suggest that when differentiated learning strategies, such as small group discussions, varied reading materials, and personalized assignments, are applied, students show increased engagement and a deeper understanding of the texts. Additionally, the model helps to create an inclusive classroom environment where students with different learning abilities can succeed and participate actively. This research highlights the importance of adapting teaching practices to meet the diverse needs of students in Madrasah Tsanawiyah, fostering not only academic success but also a more meaningful connection to religious teachings. It is expected that this study will contribute to the development of more effective teaching methods in Islamic education settings, particularly in enhancing students' engagement and comprehension of Quranic and Hadith texts.